2007
DOI: 10.3310/hta11180
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness and cost-effectiveness of cinacalcet for secondary hyperparathyroidism in end-stage renal disease patients on dialysis: a systematic review and economic evaluation

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. NHS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 76 publications
1
40
1
1
Order By: Relevance
“…By excluding ESRD costs in the main analysis but including them in a separate analysis our results can be widely compared. The cost-effectiveness with inclusion of future ESRD costs was comparable to other studies focusing on systemic anticoagulation [61], hyperphosphataemia [60], secondary hyperparathyroidism [59] and anaemia [62].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…By excluding ESRD costs in the main analysis but including them in a separate analysis our results can be widely compared. The cost-effectiveness with inclusion of future ESRD costs was comparable to other studies focusing on systemic anticoagulation [61], hyperphosphataemia [60], secondary hyperparathyroidism [59] and anaemia [62].…”
Section: Discussionsupporting
confidence: 63%
“…Our analysis confirms these earlier findings and underscores the relevance of the debate by calculating that inclusion of dialysis and renal transplant care costs double the ICER of the screen and treat strategy. Several studies in ESRD patients did not include the future costs of ESRD care [56][57][58], whereas others analysed therapies both with and without future costs [59][60][61]. By excluding ESRD costs in the main analysis but including them in a separate analysis our results can be widely compared.…”
Section: Discussionmentioning
confidence: 80%
“…111 Another cost analysis derived from the OPTIMA trial data also appears to favor cost-effectiveness of cinacalcet in five European countries, despite differences in healthcare systems and economic wealth. 112 This is contrary to the previous UK-based report 113 and ACHIEVE trial data-based simulation model, which found that cinacalcet therapy was more costly. 114 Rogerri et al analyzed FARO study data and suggested that paricalcitol treatment alone was significantly less expensive than combined with cinacalcet regardless of baseline severity and control of SHPT.…”
Section: Cinacalcet and Cost Analysiscontrasting
confidence: 55%
“…In all other patients, parathyroidectomy is the most cost-effective treatment [27] . The cost-effectiveness of long-term cinacalcet treatment was questioned by Garside et al [28] as well, who, nevertheless, used a high mean daily dose of 94 mg/day for their analysis.…”
Section: Comparison Of Direct Cost Of Medical Shpt Therapy During Andmentioning
confidence: 99%